2014
DOI: 10.1038/mt.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

Cis -splicing and Translation of the Pre- Trans -splicing Molecule Combine With Efficiency in Spliceosome-mediated RNA Trans -splicing

Abstract: Muscular dystrophies are a group of genetically distinct diseases for which no treatment exists. While gene transfer approach is being tested for several of these diseases, such strategies can be hampered when the size of the corresponding complementary DNA (cDNA) exceeds the packaging capacity of adeno-associated virus vectors. This issue concerns, in particular, dysferlinopathies and titinopathies that are due to mutations in the dysferlin (DYSF) and titin (TTN) genes. We investigated the efficacy of RNA tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…In 2012, Rindt et al demonstrated in cellular models of Huntington's disease that the mutated exon can be eliminated by 5′ replacement from the Huntingtin encoding mRNA . Recently, Monjaret et al described trans ‐splicing of the Titin pre‐mRNA, whose mutations lead to muscular dystrophies . In this study, the trans ‐spliced product was not accurately quantified and appeared clearly minor.…”
Section: Principle Advantages and Applications Of Spliceosome‐mediamentioning
confidence: 71%
See 1 more Smart Citation
“…In 2012, Rindt et al demonstrated in cellular models of Huntington's disease that the mutated exon can be eliminated by 5′ replacement from the Huntingtin encoding mRNA . Recently, Monjaret et al described trans ‐splicing of the Titin pre‐mRNA, whose mutations lead to muscular dystrophies . In this study, the trans ‐spliced product was not accurately quantified and appeared clearly minor.…”
Section: Principle Advantages and Applications Of Spliceosome‐mediamentioning
confidence: 71%
“…In the case of a recessive disease, it is likely that correcting only part of the mRNA will result in therapeutic benefit, because one ends up in the scenario of a heterozygous individual who presents no phenotype. SMaRT technology has thus been evaluated for a significant number of recessive pathologies, such as cystic fibrosis, hemophilia A, dysferlinopathies and titinopathies, X‐linked immunodeficiency with hyper‐IgM, spinal muscular atrophy, severe combined immune deficiency, Duchenne muscular dystrophy, and epidermolysis bullosa . All these studies have shown that it is possible to partially correct the cellular pool of mutated mRNA.…”
Section: Principle Advantages and Applications Of Spliceosome‐mediamentioning
confidence: 99%
“…Although RNA trans -splicing-induced RNA repair strategies were successfully applied for the restoration of gene functions in preclinical models for various diseases such as cystic fibrosis, 25, 26, 27 spinal muscular atrophy, 28, 29, 30 haemophilia A, 31 tauopathies, 32, 33 EB simplex, 34 X-linked immunodeficiency with hyper-IgM, 35 severe combined immune deficiency, 36 myotonic dystrophy type 1, 37 frontotemporal dementia with parkinsonism linked to chromosome 17, 32 Duchenne muscular dystrophy 38 and dysferlinopathy, 39 there is still scope for improvement of the trans -splicing efficiency to achieve a sustained and efficient correction of the mutated transcript. In recent studies, we have reported that the BD of the RTM is crucial for the efficiency of the trans -splicing process.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches based on 3′-replacement trans- splicing have already been used, both in vitro and in vivo , to correct several genetic diseases, including cystic fibrosis, 27 , 28 , 29 spinal muscular atrophy, 30 , 31 , 32 hemophilia A, 33 tauopathies, 34 , 35 epidermolysis bullosa simplex, 36 X-linked immunodeficiency with hyper-IgM, 37 severe combined immune deficiency, 38 myotonic dystrophy type 1, 39 frontotemporal dementia with parkinsonism linked to chromosome 17, 34 Duchenne muscular dystrophy, 40 dysferlinopathy. 41 Trans- splicing has also recently been considered as a possible basis of new strategies for treating cancer, 42 , 43 producing therapeutic proteins 44 and for molecular imaging. 45 …”
Section: Introductionmentioning
confidence: 99%